SUPER PCS. (Communications of the ACM, 2007)
This article describes the introduction of a prototype of the next generation personal computer. A team of researchers from the University of Maryland demonstrated a computer that performed tasks at 100 times the computing speed of current desktop models. The parallel processing is driven by a single chip. The circuit board is mounted with 64 parallel processors, and software programming for these coordinated processors is said to be practical and simple. The research team leader, Uzi Vishkin, has invited the public to help put a name to this new technology.